Towards an Efficient distribution system (project outreach) of Philip Morris Bangladesh Limited - Rafi, MD. Nazmus Sakib (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.